THE ANALYSIS OF INTERNAL CONTROL SYSTEM ON REVENUE CYCLE (CASE STUDY AT PT.ANGKASA PURA 1 JUANDA) - Santosa, Riezky Wahyu (Jurnal Ilmiah Mahasiswa FEB, 2017)
The objective of this research is to explore the implementation of internal control system and obstacle findings at PT. Angkasa Pura 1 Juanda. The data analysis method which has being used is qualitative descriptive analysis with a case study approach. The analysis is performed by describing or depicting factual condition of research object to find out and to analysis research problem which was faced by research object. Afterwards an alternative and suggestion were given to solve the problem. The analysis is performed based on framework Committee of Sponsoring Organization (COSO), control environment, risk assessment, information and communication, control activities, and monitoring analysis. This analysis result shows that the element of environmental control activities require a improvement that is addition of receiveable function, futhermore control activities in order to minimize the risk assessment found that is addition of finance keymaster on handle big contract by company, the information comunication and monitoring elements shows from good communication between the company leader with employees and availability of sudden inspection and evaluation. As overall, the implementation of internal control system have been applied well.Key word: Internal control system, revenue cycle, COSO framework